Social Danger of Offence in the Scientific and Legislative Definitions in Russia and Other Countries - LIPINSKY, Dmitry; MUSATKINA, Aleksandra (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The article analyzes the legislative and scientific definitions of the crime and other offences on the basis of comparative legal science. It substantiates that violations of criminal, administrative, civil, and other types of legislation have social danger. Social danger is an inherent characteristic of the offence not only according to the Russian legislation but also according to the legislation of other countries.  The purpose of this article is to corroborate the presence of the social danger characteristic not only in one type of offences – a crime, but also in different types of offences by using legislation of Russia and other countries.